Environmental impact evaluation of a European high speed railway network along the "European Silk Road" - Katharina Weber; Maximilian Zangl; Muhammad Usman Zahid; Mario Holzner (The Vienna Institute for International Economic Studies (wiiw), 2022)
In a study published in 2018 the Vienna Institute for International Economic Studies (wiiw) proposed the construction of a 'European Silk Road' encompassing a high-speed railway (HSR) network for Europe. To compliment the economic feasibility analysis by wiiw, this report aims to determine the environmental impact of the suggested northern core route - from Lyon to Moscow - by focussing on the net greenhouse-gas emissions, in CO2-eq.. The study uses a life cycle assessment (LCA) for the analysis of construction, maintenance, operation, and disposal of the HSR, to provide an estimate of how many tons of CO2-eq. can be saved over the span of 60 years. In generating a modal shift from road and air transport, the construction of an HSR line provides the potential for saving up to 10% of net CO2-eq. emissions in the EU27 for one year. Thus, the proposed high-speed line contributes to the current targets and goals of the European Union to reduce emissions and present smart, sustainable and inclusive economic solutions.
Keywords: H54; R42; L92; Q51; 330; Infrastructure; Transport; High Speed Rail; Environmental Effects